Ethical Considerations: Research with People in Situations of Forced Migration - Clark-Kazak, Christina (Refuge, 2017)
Research can contribute to better understanding of the forced migration experience to inform policy and programming, but it can also cause inconvenience and harm to research respondents.[1] In situations of forced migration, the stakes are particularly high because of precarious legal status, unequal power relations, far-reaching anti-terrorism legislation, and the criminalization of migration. In response, the Canadian Council for Refugees, York University’s Centre for Refugee Studies, and the Canadian Association for Refugee and Forced Migration Studies collaborated to complement established ethical principles with specific ethical considerations for research with people in situations of forced migration. This document highlights our guiding principles and applies the ethical concepts of voluntary, informed consent; respect for privacy; and cost-benefit analysis. It is of relevance to anyone involved in gathering information—whether in an academic or community setting—and those who are asked to take part in research.